Концепція «степових інвазій» М. Гімбутас. Спроба критичного аналізу - Конча, С.В. (Археологія, 2001)
Починаючи з 60-х років XXст. гіпотеза походження індоєвропейців із степів Східної Європи пов‘язується з ім'ям відомої американської дослідниці Марії Гімбутас. Проте конкретні культуро- та етногепетичні побудови дослідниці досі не дістали задовільного висвітлення у вітчизняній літературі. Статтю присвячено аналізу деяких ключових положень концепції М. Гімбутас з урахуванням новітніх даних і поглядів провідних дослідників. Рассматриваются построения известной американской исследовательницы Марии Гимбутас, объяснявшей кардинальные социально-культурные изменения в Европе конца V—IV тыс. до н. э. давлением и переселениями подвижных скотоводческих групп населения из глубины евразийской степной зоны. Поскольку возникшие ареалы предполагаемой метисации местного и пришлого (степного) населения культуры III тыс. до н. э. принимаются многими исследователями в качестве древнейшего несомненно этнического эквивалента носителей индоевропейских языков, правильность построений М. Гимбутас могла бы послужить доказательством гипотезы о формировании индоевропейского этноязыкового единства в степной зоне.
Однако пересмотр приводимого исследовательницей материала с учетом разработок ведущих специалистов позволяет сделать вывод, что предполагаемые инвазии степных скотоводов с достаточной убедительностью прослеживаются только в долине Дуная и части бассейна Тисы. В остальных регионах Центральной и Северной Европы материалы, подтверждающие проникновение сюда непосредственно выходцев из степной зоны или их вероятных потомков из бассейна Дуная, не обнаружены, что признается и современными сторонниками «степной» версии прародины индоевропейцев. The article deals with the constructions of the well-known American researcher Maria Gimbutas, who explained the cardinal socio-cultural changes in Europe at the end of the 5-4 millennium BC by the pressure and migration of mobile cattle-breeding groups of the population from the heart of the Eurasian steppe zone. Since many of researchers regard the cultures of the III millennium BC, which arose in the habitat of the supposed miscegenation of the local and alien (steppe) populations, as the most ancient unquestionable ethnic equivalent of native speakers of Indo-European languages, the accuracy of M. Gimbutas’ constructions would become a proof of the hypothesis about the formation of the Indo-European ethnic and lingual unity in the steppe zone.
However, the revision of the material, which is given by the researcher, concerning the works of the leading experts allows one to conclude that the supposed invasions of steppe cattle breeders are traced with sufficient cogency only in the Danube Valley and in a part of the Tisza’s basin. In other regions of Central and Northern Europe, no materials, that would confirm the penetration of the population directly from the steppe zone or their probable descendants from the Danube’s basin into this region, were discovered. This fact is recognized also by the modern followers of the «steppe» version for the forefather land of the Indo-Europeans.